Histidine Metabolism and IGPD Play a Key Role in Cefquinome Inhibiting Biofilm Formation of Staphylococcus xylosus - Zhou, Yong-hui; Xu, Chang-geng; Yang, Yan-bei; Xing, Xiao-xu; Liu, Xin; Qu, Qian-wei; Ding, Wen-ya; Bello-Onaghise, God’spower; Li, Yan-hua (Frontiers in Microbiology, 2018)
Staphylococcus xylosus (S. xylosus) is an AT-rich and coagulase-negative Staphylococcus (CNS). It is normally regarded as non-pathogenic, however recent studies have demonstrated that it is related to human opportunistic infections and bovine mastitis. In addition, S. xylosus strains have the ability to form biofilm. Biofilms are also involved in chronic infections and antibiotic resistance, there are only a few reports about cefquinome inhibiting S. xylosus biofilm formation and the protein targets of cefquinome. In our study, we found that sub-MICs of cefquinome were sufficient to inhibit biofilm formation. To investigate the potential protein targets of cefquinome, we used iTRAQ for the analyses of cells at two different conditions: 1/2-MIC (0.125μg/mL) cefquinome treatment and no treatment. Using iTRAQ technique and KEGG database analysis, we found that proteins differently expression in histidine metabolism pathway may play a role in the process by which 1/2-MIC (0.125 μg/mL) cefquinome inhibits S. xylosus biofilm formation. Interestingly, we found a sharply down-regulated enzyme (A0A068E9J3 imidazoleglycerol-phosphate dehydratase, IGPD) involved in histidine metabolism pathway in cefquinome-treated cells. We demonstrated the important role of IGPD in sub-MICs cefquinome inhibiting biofilm formation of S. xylosus by gene (hisB) knockout, IGPD enzyme activity and histidine content assays. Thus, our data sheds light on important role of histidine metabolism in S. xylosus biofilm formation; especially, IGPD involved in histidine metabolism might play a crucial role in sub-MICs cefquinome inhibition of biofilm formation of S. xylosus, and we propose IGPD as an attractive protein target of cefquinome.